Method for preparing aromatic hydrocarbon by catalyzing carbon dioxide hydrogenation
The use of a CuFeO2 and ordered stacked multilayer HZSM-5 nanosheets bifunctional catalyst addresses the mass transfer and diffusion limitations in existing methods, enhancing the yield and selectivity of aromatic hydrocarbons through optimized hydrogenation of carbon dioxide.
Patent Information
- Application Number
- CN202411172072.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2024-12-13
AI Technical Summary
Existing methods for catalytic hydrogenation of carbon dioxide to produce aromatics face challenges in mass transfer and diffusion performance of HZSM-5 molecular sieves, leading to low selectivity and yield of aromatic products.
A bifunctional catalyst composed of CuFeO2 and ordered stacked multilayer HZSM-5 nanosheets is used, with a specific structure and preparation method to enhance mass transfer and diffusion, including a hydrothermal synthesis process and reduction conditions to improve aromatization.
The catalyst significantly increases the yield of aromatic hydrocarbons, achieving a CO2 conversion rate of 59%, aromatics selectivity of 68%, and a yield of 490 mg CH2·gcat-1·h-1, with improved aromatization capacity and product distribution.
Smart Images

Figure BDA0005009573970000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalytic technology, and specifically relates to a method for preparing aromatic hydrocarbons by catalytic hydrogenation of carbon dioxide (CO2+H2). Background Art
[0002] Aromatics and light aromatics are important raw materials for basic chemicals. They are not only widely used in high-end fields such as aerospace and mobile communications, but also have huge demand in civilian fields such as clothing fabrics and transportation. At present, my country's annual consumption of aromatics is more than 20 million tons. However, aromatics are almost produced from petroleum. The development of the aromatics industry has been greatly restricted due to its heavy reliance on imported petroleum. In addition, in the process of using petroleum resources to produce aromatics, a large amount of carbon dioxide is emitted into the atmosphere, causing serious environmental problems. Therefore, the method of using carbon dioxide combined with renewable hydrogen to produce aromatics is a promising green development path for the production of aromatics.
[0003] In recent years, the technology of catalytic hydrogenation of carbon dioxide to produce aromatics has been extensively studied. The technology of using iron-based catalysts coupled with HZSM-5 molecular sieves to catalyze the hydrogenation of carbon dioxide to produce aromatics has received widespread attention. However, during aromatization, the intermediate product olefins are limited by the mass transfer and diffusion performance of HZSM-5, which not only affects the stability and activity of the bifunctional catalyst, but also affects the selectivity and yield of the product aromatics. Therefore, there is still a lot of room for improvement in the improvement of aromatic products, such as improving the selectivity and yield of aromatic products. Changing the morphology and structure of HZSM-5, improving the distribution of aromatic products, and improving the selectivity and yield of aromatics have become the focus of current research. The team of Sun Jian and Ge Qingjie (Nature Communications, 2017, 8 (1): 15174) synthesized a new Na-Fe3O4 / HZSM-5 multifunctional composite catalyst by a one-pot method. Although the catalyst preparation method is simple, under the influence of HZSM-5, the conversion rate of CO2 and the yield of aromatics are both low. Liu Dianhua's team (ACS Catalysis, 2020, 10(19): 11268-11279) used Cu to modify the Fe2O3 catalyst and coupled HZSM-5 to form a bifunctional catalyst 6.25Cu-Fe2O3 / HZSM-5-c. Although they achieved good CO2 conversion and aromatics selectivity, the low reaction space velocity resulted in an extremely low aromatics yield. Sun Yuhan's team (ACS Catalysis, 2019, 9(5): 3866-3876) passivated the acid centers on the outer surface of HZSM-5 to prepare ZnFeO x-4.25Na / S-ZSM-5-Si catalyst improves the selectivity of aromatics and para-xylene, but the silicon coating reduces the acidity and mass transfer diffusion performance of the molecular sieve, and also significantly reduces the yield of aromatics. Wang Chenguang's research group (Energy & Fuels, 2020, 34(9): 11282-11289) used Na to modify the Fe-based catalyst and prepared Na-Fe3O4 coupled HZSM-5 to form 1Na-Fe / HZSM-5 catalyst by co-precipitation. Although the highly acidic HZSM-5 has better catalytic performance, the yield of aromatics is still low. Wei Fei's team (Catalysis Science & Technology, 2020, 10(10): 3366-3375) prepared short b-axis HZSM-5 and coupled it with Mn2O3 to obtain Mn2O3 / HZSM-5 catalyst, which can achieve a high hydrocarbon aromatic selectivity of 83%. However, due to the methanol route, the reaction temperatures of the two catalysts did not match, and the selectivity of by-products CH4 and CO was too high. Summary of the invention
[0004] The purpose of the present invention is to provide a method for directly preparing aromatic hydrocarbons by catalytic hydrogenation of carbon dioxide, which improves the mass transfer and diffusion performance of HZSM-5 molecular sieve by orderly stacking multi-layer HZSM-5 nanosheets and increases the yield of aromatic hydrocarbons.
[0005] In view of the above purpose, the technical solution adopted by the present invention is: a bifunctional catalyst is filled in a fixed bed reactor, wherein the bifunctional catalyst is a mixture of a CuFeO2 catalyst and an ordered stacked multilayer HZSM-5 nanosheet; the ordered stacked multilayer HZSM-5 nanosheet presents an ordered stacking structure along the b axis, with a sheet thickness of 10 to 60 nm, a stacking thickness of 100 to 1000 nm, a silicon-aluminum ratio of 15 to 30, and a specific surface area of 250 to 350 m 2 / g, pore volume 0.15~0.3cm 3 / g, pore size 0.1-0.8nm, interlamellar spacing 1-3nm; before the reaction, hydrogen is first passed to reduce the CuFeO2 catalyst, and the reduction conditions are: temperature 350-450℃, time 1-10h, pressure 0.1MPa-1MPa, mass space velocity 9000-14000mL·h -1 ·g -1 Then, carbon dioxide and hydrogen are introduced to react. The reaction conditions are: temperature 300-340°C, pressure 1-5 MPa, H2 / CO2 molar ratio 1-5:1, mass space velocity 6000-10000 mL·h -1 ·g -1 .
[0006] In the above-mentioned bifunctional catalyst, the mass ratio of the CuFeO2 catalyst to the ordered stacked multilayer HZSM-5 nanosheets is preferably 0.5 to 3:1.
[0007] Furthermore, the CuFeO2 catalyst and the ordered stacked multilayer HZSM-5 nanosheet mixture are respectively tableted and crushed before loading, passed through a 20-40 mesh sieve, and then mixed evenly.
[0008] The preparation method of the above-mentioned CuFeO2 catalyst is as follows: dissolve ferric nitrate nonahydrate and cupric nitrate trihydrate in deionized water, mix them evenly, add sodium hydroxide particles, control the system to be in an alkaline environment, then add propionaldehyde, and finally load it into a hydrothermal kettle, hydroheat it at 180°C for 24 hours, centrifuge it, and vacuum dry the obtained filter cake at 60°C to obtain a CuFeO2 catalyst; wherein the mass ratio of the ferric nitrate nonahydrate, cupric nitrate trihydrate, and propionaldehyde is 1:0.6:0.25.
[0009] The method for preparing the ordered stacked multilayer HZSM-5 nanosheets comprises the following steps:
[0010] Step 1: dissolving tetraethyl orthosilicate and tetrapropylammonium hydroxide in deionized water, stirring at room temperature for 8 to 36 hours, and then hydrothermally treating at 60 to 120° C. for 12 to 36 hours to obtain a silicate seed sol; wherein the mass ratio of tetraethyl orthosilicate to tetrapropylammonium hydroxide to deionized water is 1:1.2 to 1.6:0.4 to 0.8;
[0011] Step 2: adding aluminum isopropoxide to a 0.01-0.05 g / mL potassium hydroxide aqueous solution, stirring at room temperature for 2-5 hours to obtain solution A; adding tetraethyl orthosilicate to a 0.01-0.05 g / mL potassium hydroxide aqueous solution, stirring at room temperature for 2-5 hours to obtain solution B; then adding solution A to solution B, stirring for another 3-8 hours to form a uniform gel C; dissolving hexadecyltrimethylammonium bromide in a 0.01-0.05 g / mL potassium hydroxide aqueous solution at 65°C, stirring for 1-3 hours, and then adding it to a silicate seed sol to form a uniform gel D; adding gel D to gel C, stirring for 1-3 hours to obtain a mixture E; wherein the mass ratio of tetraethyl orthosilicate to aluminum isopropoxide, the total mass of potassium hydroxide, hexadecyltrimethylammonium bromide, and the silicate seed sol is 1:0.03-0.08:0.1-0.2:0.05-1.5:1-2;
[0012] Step 3: The mixture E obtained in step 2 is charged into a hydrothermal reactor, and the mixture is subjected to a hydrothermal reaction at 150-190° C. for 48-94 hours, and then cooled to room temperature after the reaction is completed; the obtained precipitate is washed with deionized water, and then dried at 80-100° C. for 5-12 hours, and the obtained white powder is calcined at 500-600° C. for 2-8 hours to obtain ordered stacked multilayer ZSM-5 nanosheets;
[0013] Step 4: placing the ordered stacked multilayer ZSM-5 nanosheets obtained in step 3 in an aqueous solution of ammonium fluoride, stirring at 70-90° C. for ammonium ion exchange, and then filtering, washing, and calcining to obtain ordered stacked multilayer HZSM-5 nanosheets.
[0014] In the above step 1, tetraethyl orthosilicate and tetrapropylammonium hydroxide are preferably dissolved in deionized water, stirred at room temperature for 12 to 24 hours, and then hydrothermally treated at 80 to 100° C. for 18 to 24 hours to obtain a silicate seed sol.
[0015] In the above step 3, the mixture E obtained in step 2 is preferably charged into a hydrothermal kettle and subjected to hydrothermal reaction at 170-180° C. for 60-80 h.
[0016] In the above step 4, the concentration of the ammonium fluoride aqueous solution is preferably 1 to 2 mol / L.
[0017] In the above step 4, the calcination temperature is preferably 500-600° C. and the calcination time is 2-8 hours.
[0018] In the above-mentioned method for preparing aromatic hydrocarbons by catalytic hydrogenation of carbon dioxide, the reduction conditions of the CuFeO2 catalyst are preferably: temperature 380-420°C, time 1-4h, pressure 0.1MPa-0.5MPa, mass space velocity 10000-13000mL·h -1 ·g -1 .
[0019] The above-mentioned method for preparing aromatic hydrocarbons by catalytic hydrogenation of carbon dioxide, preferably the reaction conditions are: temperature 310-330°C, pressure 2-4MPa, H2 / CO2 molar ratio 1-3:1, mass space velocity 7000-9000mL·h -1 ·g -1 .
[0020] The present invention has the following beneficial effects:
[0021] 1. The present invention compresses, crushes and mechanically mixes CuFeO2 catalyst and ordered stacked multi-layer HZSM-5 nanosheets, and then loads them into a fixed bed reactor as a bifunctional catalyst for catalyzing the hydrogenation of carbon dioxide to prepare aromatics. Among them, short b-axis layer HZSM-5 is obtained by using CTAB as a growth inhibitor during the hydrothermal synthesis of HZSM-5 molecular sieve, and at the same time, the self-assembly behavior of CTAB in the solution guides the generation of ordered stacked multi-layer HZSM-5 nanosheets, and a quasi-mesoporous structure is constructed between the closely arranged layers, which increases the mass transfer and diffusion capacity and improves the aromatization capacity of the molecular sieve, fully converts the intermediate olefins obtained by the CuFeO2-catalyzed carbon dioxide hydrogenation reaction, and obtains more aromatic products and a higher aromatic yield.
[0022] 2. The catalyst used in the method of the present invention is simple to prepare, low-cost, green and pollution-free. Compared with the traditional HZSM-5 molecular sieve, the use of this catalyst significantly promotes the aromatization reaction, improves the product distribution, and greatly increases the proportion and yield of aromatics. The performance of the catalyst was evaluated on a fixed bed reactor, with a CO2 conversion rate of about 59%, an aromatics selectivity of about 68%, and a yield of 490 mg. CH2 ·gcat -1 ·h -1 It has good industrial application prospects. DETAILED DESCRIPTION
[0023] The present invention is further described in detail below in conjunction with the embodiments, but the protection scope of the present invention is not limited to these embodiments.
[0024] Example 1
[0025] 1. Preparation of CuFeO2 Catalyst
[0026] Dissolve 8.0g of ferric nitrate nonahydrate and 4.8g of copper nitrate trihydrate in 160mL of deionized water, mix well, add 16g of sodium hydroxide particles, control the system to be in an alkaline environment, then add 2g of propionaldehyde, and finally load into a 200mL hydrothermal kettle, hydrothermally react at 180°C for 24 hours, centrifuge and filter after the reaction, and vacuum dry the obtained filter cake at 60°C to obtain a CuFeO2 catalyst.
[0027] 2. Preparation of ordered stacked multilayer HZSM-5 nanosheets
[0028] Step 1: Dissolve 19.9 g of tetraethyl orthosilicate and 27.9 g of tetrapropylammonium hydroxide in 12.1 g of deionized water, stir at room temperature for 24 hours, and then perform hydrothermal treatment at 80° C. for 24 hours to obtain a silicate seed sol.
[0029] Step 2: Dissolve 0.9 g of potassium hydroxide in 35.6 g of deionized water under magnetic stirring to obtain a potassium hydroxide aqueous solution; slowly add 0.27 g of aluminum isopropoxide to 10 g of potassium hydroxide aqueous solution, and vigorously stir at room temperature for 2 hours to obtain solution A; slowly add 6.8 g of tetraethyl orthosilicate to 15.6 g of potassium hydroxide aqueous solution, and vigorously stir at room temperature for 2 hours to obtain solution B; then slowly add solution A to solution B, and vigorously stir for 5 hours to form a uniform gel C; dissolve 0.72 g of hexadecyltrimethylammonium bromide in 10 g of potassium hydroxide aqueous solution at 65°C, stir for 1 hour, and then slowly add to 8.8 g of silicate seed sol to form a uniform gel D; slowly add gel D to gel C, stir for 1 hour, and obtain mixture E.
[0030] Step 3: The mixture E obtained in step 2 is charged into a hydrothermal kettle and subjected to hydrothermal reaction at 175°C for 72 hours. The mixture is cooled to room temperature, the precipitate is washed with deionized water and dried in an oven at 100°C for 8 hours. The white powder is calcined in a muffle furnace at 550°C for 6 hours to obtain ordered stacked multilayer ZSM-5 nanosheets.
[0031] Step 4: Place the ordered stacked multilayer ZSM-5 nanosheets obtained in step 3 in a 1 mol / L ammonium fluoride aqueous solution, stir in a water bath at 80°C for ammonium ion exchange, and then filter, wash, and calcine at 550°C for 6 hours to obtain ordered stacked multilayer HZSM-5 nanosheets with a sheet thickness of about 45 nm, a stacking thickness of about 250 nm, a silicon-aluminum ratio of 21.6, and a specific surface area of 293.6 m 2 / g, pore volume 0.23cm 3 / g, pore diameter is about 0.4nm, and interlamellar spacing is about 2nm.
[0032] 3. Catalytic hydrogenation of carbon dioxide to produce aromatics
[0033] The CuFeO2 catalyst and the ordered stacked multilayer HZSM-5 nanosheets were pressed and crushed at a mass ratio of 2:1, passed through a 20-40 mesh sieve, and then the two were mixed evenly and filled into the constant temperature section of a fixed bed reactor. Before the reaction, the CuFeO2 catalyst was reduced by hydrogen, and the reduction conditions were: temperature 400°C, time 2h, pressure 0.1MPa, mass space velocity 12000mL·h -1 ·g -1 Then, carbon dioxide and hydrogen were introduced for reaction. The reaction conditions were: temperature 320°C, pressure 3MPa, H2 / CO2 molar ratio 3:1, mass space velocity 8100mL·h -1 ·g -1 The reaction results are shown in Table 1.
[0034] Example 2
[0035] In this embodiment, the preparation method of CuFeO2 catalyst is the same as that in Example 1, and ordered stacked multilayer HZSM-5 nanosheets are prepared according to the method in Example 1, except that the added mass of aluminum isopropoxide is 0.22 g, the sheet thickness of the ordered stacked multilayer HZSM-5 nanosheets is about 47 nm, the stacking thickness is about 260 nm, the silicon-aluminum ratio is 27.5, and the specific surface area is 312.23 m 2 / g, pore volume 0.24cm 3 / g, pore diameter of about 0.4nm, interlamellar spacing of about 2nm. Then, the catalytic carbon dioxide hydrogenation to aromatics reaction was carried out according to the method of Example 1, and the results are shown in Table 1.
[0036] Example 3
[0037] In this embodiment, the preparation method of CuFeO2 catalyst is the same as that of Example 1, and the ordered stacked multilayer HZSM-5 nanosheets are prepared according to the method of Example 1, except that the added mass of hexadecyltrimethylammonium bromide is 0.6 g, the sheet thickness of the ordered stacked multilayer HZSM-5 nanosheets is about 10 nm, the stacking thickness is about 110 nm, the silicon-aluminum ratio is 22.8, and the specific surface area is 301.71 m 2 / g, pore volume 0.21cm 3 / g, pore diameter of about 0.4nm, interlamellar spacing of about 2nm. Then, the catalytic carbon dioxide hydrogenation to aromatics reaction was carried out according to the method of Example 1, and the results are shown in Table 1.
[0038] Example 4
[0039] In this embodiment, the preparation method of CuFeO2 catalyst is the same as that of Example 1, and ordered stacked multilayer HZSM-5 nanosheets are prepared according to the method of Example 1, except that the added mass of hexadecyltrimethylammonium bromide is 0.36 g, the sheet thickness of the ordered stacked multilayer HZSM-5 nanosheets is about 45 nm, the stacking thickness is about 250 nm, the silicon-aluminum ratio is 21.6, and the specific surface area is 293.6 m 2 / g, pore volume 0.23cm 3 / g, pore diameter of about 0.4nm, interlamellar spacing of about 2nm. Then, the catalytic carbon dioxide hydrogenation to aromatics reaction was carried out according to the method of Example 1, and the results are shown in Table 1.
[0040] Example 5
[0041] In this embodiment, the preparation method of the CuFeO2 catalyst is the same as that of Example 1, and ordered stacked multilayer HZSM-5 nanosheets are prepared according to the method of Example 1. Then, the catalytic carbon dioxide hydrogenation to aromatics reaction is carried out according to the method of Example 1, except that the pressure of the hydrogenation to aromatics reaction is 3.5 MPa. The results are shown in Table 1.
[0042] Example 6
[0043] In this embodiment, the preparation method of the CuFeO2 catalyst is the same as that of Example 1, and ordered stacked multilayer HZSM-5 nanosheets are prepared according to the method of Example 1. Then, the catalytic carbon dioxide hydrogenation to aromatics reaction is carried out according to the method of Example 1, except that the mass ratio of the CuFeO2 catalyst to the ordered stacked multilayer HZSM-5 nanosheets in the bifunctional catalyst is 1:1. The results are shown in Table 1.
[0044] Comparative Example 1
[0045] The CuFeO2 catalyst of Example 1 and commercial HZSM-5 molecular sieve (silicon-aluminum ratio of 25, purchased from Nankai Molecular Sieve Factory) were tableted and crushed at a mass ratio of 2:1, passed through a 20-40 mesh sieve, and then mixed evenly and filled in the constant temperature section of a fixed bed reactor. The catalytic carbon dioxide hydrogenation to aromatics reaction was carried out according to the method of Example 1. The results are shown in Table 1.
[0046] Comparative Example 2
[0047] The CuFeO2 catalyst of Example 1 and commercial HZSM-5 molecular sieve (silicon-aluminum ratio of 35, purchased from Nankai Molecular Sieve Factory) were tableted and crushed at a mass ratio of 2:1, passed through a 20-40 mesh sieve, and then the two were mixed evenly and filled in the constant temperature section of a fixed bed reactor. The catalytic carbon dioxide hydrogenation to aromatics reaction was carried out according to the method of Example 1. The results are shown in Table 1.
[0048] Comparative Example 3
[0049] The bifunctional 6.25Cu-Fe2O3 / HZSM-5-c catalyst described in the literature (ACS Catalysis, 2020, 10(19): 11268-11279) was used to catalyze the hydrogenation of carbon dioxide to produce aromatics. The mass ratio of 6.25Cu-Fe2O3 to HZSM-5-c in the catalyst was 1:1. The reaction conditions were: temperature 320°C, pressure 3.0 MPa, H2 / CO2 / N2 molar ratio = 72 / 24 / 4, and mass space velocity 1000 mL·h -1 ·g -1 The reaction results are shown in Table 1.
[0050] Table 1 Results of catalytic CO2 hydrogenation conversion using different catalysts
[0051]
[0052] As can be seen from Table 1, thanks to the self-assembly behavior of CTAB as a surfactant, it forms layered micelles under the interaction with the HZSM-5 seed crystals during hydrothermal synthesis, leading to the synthesis of ordered stacked multilayer HZSM-5 nanosheets. Compared with the thick layer structure of commercial HZSM-5, it can improve the mass transfer and diffusion effect, and reduce the limitation of the single microporous structure of HZSM-5 on the aromatization reaction. Orderly stacked multilayer HZSM-5 nanosheets can promote the aromatization reaction of olefins, effectively promoting the further aromatization of olefins to aromatic products. The reaction conditions are: temperature 320℃, pressure 3MPa, H2 / CO2 molar ratio 3:1, mass space velocity 8100mL·h -1 ·g -1 Under the condition of , the reaction has a high CO2 conversion rate of 59.9%, aromatics selectivity of 68.4%, and aromatics space-time yield of 490.9mg CH2 ·gcat -1 ·h -1 .
Claims
1. A method for preparing aromatic hydrocarbons by catalytic hydrogenation of carbon dioxide, characterized in that: A bifunctional catalyst is filled in a fixed bed reactor, wherein the bifunctional catalyst is a mixture of a CuFeO2 catalyst and ordered stacked multilayer HZSM-5 nanosheets; the ordered stacked multilayer HZSM-5 nanosheets present an ordered stacking structure along the b axis, with a sheet thickness of 10 to 60 nm, a stacking thickness of 100 to 1000 nm, a silicon-aluminum ratio of 15 to 30, and a specific surface area of 250 to 350 m 2 / g, pore volume 0.15~0.3cm 3 / g, pore size 0.1-0.8nm, interlamellar spacing 1-3nm; before the reaction, hydrogen is first passed to reduce the CuFeO2 catalyst, and the reduction conditions are: temperature 350-450℃, time 1-10h, pressure 0.1MPa-1MPa, mass space velocity 9000-14000mL·h -1 ·g -1 Then, carbon dioxide and hydrogen are introduced to react. The reaction conditions are: temperature 300-340°C, pressure 1-5 MPa, H2 / CO2 molar ratio 1-5:1, mass space velocity 6000-10000 mL·h -1 ·g -1 .
2. The method for preparing aromatics by catalytic hydrogenation of carbon dioxide according to claim 1, characterized in that: The mass ratio of the CuFeO2 catalyst to the ordered stacked multilayer HZSM-5 nanosheets in the bifunctional catalyst is 0.5 to 3:
1.
3. The method for preparing aromatic hydrocarbons by catalytic hydrogenation of carbon dioxide according to claim 1, characterized in that: The CuFeO2 catalyst and the ordered stacked multi-layer HZSM-5 nanosheet mixture are respectively tableted and crushed before filling, passed through a 20-40 mesh sieve, and then mixed evenly.
4. The method for preparing aromatics by catalytic hydrogenation of carbon dioxide according to any one of claims 1 to 3, characterized in that: The method for preparing ordered stacked multilayer HZSM-5 nanosheets comprises the following steps: Step 1: dissolving tetraethyl orthosilicate and tetrapropylammonium hydroxide in deionized water, stirring at room temperature for 8 to 36 hours, and then hydrothermally treating at 60 to 120° C. for 12 to 36 hours to obtain a silicate seed sol; wherein the mass ratio of tetraethyl orthosilicate to tetrapropylammonium hydroxide to deionized water is 1:1.2 to 1.6:0.4 to 0.8; Step 2: adding aluminum isopropoxide to a 0.01-0.05 g / mL potassium hydroxide aqueous solution, stirring at room temperature for 2-5 hours to obtain solution A; adding tetraethyl orthosilicate to a 0.01-0.05 g / mL potassium hydroxide aqueous solution, stirring at room temperature for 2-5 hours to obtain solution B; then adding solution A to solution B, stirring for another 3-8 hours to form a uniform gel C; dissolving hexadecyltrimethylammonium bromide in a 0.01-0.05 g / mL potassium hydroxide aqueous solution at 65°C, stirring for 1-3 hours, and then adding it to a silicate seed sol to form a uniform gel D; adding gel D to gel C, stirring for 1-3 hours to obtain a mixture E; wherein the mass ratio of tetraethyl orthosilicate to aluminum isopropoxide, the total mass of potassium hydroxide, hexadecyltrimethylammonium bromide, and the silicate seed sol is 1:0.03-0.08:0.1-0.2:0.05-1.5:1-2; Step 3: The mixture E obtained in step 2 is charged into a hydrothermal reactor, and the mixture is subjected to a hydrothermal reaction at 150-190° C. for 48-94 hours, and then cooled to room temperature after the reaction is completed; the obtained precipitate is washed with deionized water, and then dried at 80-100° C. for 5-12 hours, and the obtained white powder is calcined at 500-600° C. for 2-8 hours to obtain ordered stacked multilayer ZSM-5 nanosheets; Step 4: placing the ordered stacked multilayer ZSM-5 nanosheets obtained in step 3 in an aqueous solution of ammonium fluoride, stirring at 70-90° C. for ammonium ion exchange, and then filtering, washing, and calcining to obtain ordered stacked multilayer HZSM-5 nanosheets.
5. The method for preparing aromatics by catalytic hydrogenation of carbon dioxide according to claim 4, characterized in that: In step 1, tetraethyl orthosilicate and tetrapropylammonium hydroxide are dissolved in deionized water, stirred at room temperature for 12 to 24 hours, and then hydrothermally treated at 80 to 100° C. for 18 to 24 hours to obtain a silicate seed sol.
6. The method for preparing aromatics by catalytic hydrogenation of carbon dioxide according to claim 4, characterized in that: In step 3, the mixture E obtained in step 2 is charged into a hydrothermal kettle and subjected to hydrothermal reaction at 170-180° C. for 60-80 h.
7. The method for preparing aromatic hydrocarbons by catalytic hydrogenation of carbon dioxide according to claim 4, characterized in that: In step 4, the concentration of the ammonium fluoride aqueous solution is 1-2 mol / L.
8. The method for preparing aromatic hydrocarbons by catalytic hydrogenation of carbon dioxide according to claim 4, characterized in that: In step 4, the calcination temperature is 500-600° C. and the calcination time is 2-8 hours.
9. The method for preparing aromatic hydrocarbons by catalytic hydrogenation of carbon dioxide according to claim 1, characterized in that: The reduction conditions of the CuFeO2 catalyst are: temperature 380-420°C, time 1-4h, pressure 0.1MPa-0.5MPa, mass space velocity 10000-13000mL·h -1 ·g -1 .
10. The method for preparing aromatic hydrocarbons by catalytic hydrogenation of carbon dioxide according to claim 1, characterized in that: The reaction conditions are: temperature 310-330°C, pressure 2-4MPa, H2 / CO2 molar ratio 1-3:1, mass space velocity 7000-9000mL·h -1 ·g -1 .
Citation Information
Cited By
Catalyst for preparing aromatic aviation kerosene as well as preparation method and application of catalyst
CN122499827A
A catalyst for producing aromatic hydrocarbon-based aviation kerosene, a preparation method thereof, and an application thereof
CN122499827B
